Literary drowning : postcolonial memory in Irish and Caribbean writing - Boeninger, Stephanie Pocock (Irish studies, 2020)
""Literary Drowning" is the first book-length study of drowning in literature. It examines depictions of the drowned body in Irish and Caribbean postcolonial literature, uncovering a complex transatlantic conversation that re-evaluates memory, forgetfulness, and the role that each plays in the construction of the postcolonial subject and nation"--